Strategic Monolingualism and Multimodal Accommodation in Global Tech Keynotes: A Sociolinguistic Analysis of Apple, Google, and Samsung - Muhammad Nur Assyddyq; Listya Arum Ridhawati; Mentari Antika Putri (Universitas Islam Negeri Palopo, 2025)
This research examines strategic monolingualism as an accommodation strategy in global technology keynotes, analyzing thirty presentations from Apple, Google, and Samsung (2020–2024). Research has shown that code-switching is a good way to find a balance between global and local needs. However, tech companies only use English to reach multilingual audiences, which is strange. How do monolingual presentations reach a global audience without using different languages? Quantitative analysis shows that there is a more direct address, more inclusive pronouns, and less hedging, which creates corporate certainty. Qualitative analysis indicates that multimodal resources—such as live demonstrations, accessibility features, cultural framing, and synchronized visuals—serve as meaning-making alternatives (semiotic substitution) to code-switching. Instead of switching languages, businesses switch between different ways of communicating (visual, verbal, musical) to get things done. Drawing from Communication Accommodation Theory, Politeness Theory, and Multimodal Discourse Analysis, the study identifies strategic monolingualism as a transition wherein various modes collaborate to engage diverse audiences, supplanting conventional bilingual accommodation. This pattern—linguistic homogeneity facilitating semiotic heterogeneity—redefines accommodation beyond code-switching frameworks. The results help teachers of English for Specific Purposes by showing that multimodal literacy is important for professional communication. They also help business people who need to balance brand consistency with global engagement by giving them a Multimodal Accommodation Framework.